2017
DOI: 10.3233/adr-170031
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mindfulness on Older Adults with Mild Cognitive Impairment

Abstract: Background:The current lack of an effective cure for dementia would exacerbate its prevalence and incidence globally. Growing evidence has linked mindfulness to cognitive and psychological improvements that could be relevant for mild cognitive impairment (MCI).Objective:To investigate whether mindfulness practice can improve health outcomes of MCI.Methods:The study is the first longitudinal mixed-methods observational study with a one-year follow-up period, that customized an eight-week group-based mindfulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 49 publications
4
91
0
1
Order By: Relevance
“…Several recent reviews of meditation interventions (of either Kirtan Kriya Meditation or mindfulness-based programs) [64] and yoga interventions [65] report on 11 additional studies [66][67][68][69][70][71][72][73][74][75][76][77][78] that have demonstrated benefits in adults with subjective cognitive decline, MCI, and AD. Since these reviews, an additional study of tai chi in older adults at risk for cognitive decline has been published, [79] along with mindfulness studies in adults with subjective cognitive decline, [80,81] MCI, [82] and dementia. [83,84] The study designs and outcomes from these studies are very heterogeneous, and most studies were small and considered pilot/feasibility (except for two studies with sample sizes over 110 [70,79]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent reviews of meditation interventions (of either Kirtan Kriya Meditation or mindfulness-based programs) [64] and yoga interventions [65] report on 11 additional studies [66][67][68][69][70][71][72][73][74][75][76][77][78] that have demonstrated benefits in adults with subjective cognitive decline, MCI, and AD. Since these reviews, an additional study of tai chi in older adults at risk for cognitive decline has been published, [79] along with mindfulness studies in adults with subjective cognitive decline, [80,81] MCI, [82] and dementia. [83,84] The study designs and outcomes from these studies are very heterogeneous, and most studies were small and considered pilot/feasibility (except for two studies with sample sizes over 110 [70,79]).…”
Section: Discussionmentioning
confidence: 99%
“…Participants randomized to these interventions showed some improvements in measures of cognition, specifically in executive function, attention, and verbal memory. Three of the studies with long-term follow-up of one-two years [70,79,82] found that the mindfulness interventions may help preserve global cognition, with one study showing that those who meditated more had greater improvements in cognitive function (p<0.05). [82] Emotional reactivity, psychological well-being, perceived stress, mood, quality of life, subjective sleep quality, and mindfulness were all measures that improved as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could potentially translate to downstream significance of better quality of life and higher work productivity of persons with MCI and their FSP, and a reduced chronic disease burden on families of persons with MCI and the healthcare system. If effective, “partnerships could be eventually forged with the Alzheimer's Australia and memory clinics/services such as the CDAMS to deliver the customized group mindfulness training program to the target population of persons with MCI and their FSP” (Wong et al, 2015 ).…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…The positive effects of meditation on cognition and dementia risk reduction may be achieved holistically through multiple pathways such as producing neuroprotective effects from less stress-induced cortisol secretion with higher brain-derived neurotrophic factor (BDNF) levels; enhancing lipid profiles and reducing oxidative stress, thereby reducing risk for cerebrovascular/age-related neurodegenerative diseases; and reinforcing neuronal circuits and boosting cognitive reserve (Xiong and Doraiswamy, 2009 ). Moreover, “studies have demonstrated the effects of mindfulness on enlarging gray matter volume (Pagnoni and Cekic, 2007 ; Luders et al, 2009 ), increasing gray matter concentration (Hölzel et al, 2008 ; Vestergaard-Poulsen et al, 2009 ; Hölzel et al, 2011 ; Singleton et al, 2014 ), strengthening brain functional connectivity (Brewer et al, 2011 ; Jang et al, 2011 ; Hasenkamp and Barsalou, 2012 ; Taylor et al, 2013 ; Wells et al, 2013b ), and enhancing psychological well-being (Singleton et al, 2014 ), thus suggesting the potential benefits of mindfulness on MCI” (Wong et al, 2015 ). Mindfulness can thus prevent the “tissue volume loss in the hippocampus and posterior cingulate/precuneus (Buckner et al, 2005 ; Beason-Held, 2011 ; Fotuhi et al, 2012 ; Wang et al, 2013 ), gradual loss of gray matter (Thompson et al, 2003 ), reduced functional connectivity in the default mode network (Sorg et al, 2007 ; Gili et al, 2011 ; Hafkemeijer et al, 2012 ; Wang et al, 2013 ), and high chronic psychological distress (Wilson et al, 2007 ) that are all implicated in the memory and cognitive decline observed in MCI and AD” (Wong et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%